Enhancing speaking proficiency through task-based activities: A systematic literature review in the TVET Context - Mohd Khirulnizam, Musa; Azwin Arif, Abdul Rahim; Nor Yazi, Khamis (e-International Publishing House, 2025)
Speaking proficiency is important to TVET learners as they prepare for workplace communication. This systematic literature review explores the use of task-based language teaching (TBLT) for improving speaking in TVET context. Following the PRISMA framework, we included and analyzed twelve studies in the from Scopus and Web of Science. Three themes were identified in the review: (1) task-based speaking activity design, (2) learners’ communicative competence and (3) trends and gaps in TBLT research. The results emphasize the need for real tasks, learner interaction and more research in digital tools and teacher preparedness in TVET contexts.